Creating more and better employment in agrifood systems - Berdegué, Julio A.; Trivelli, Carolina; Corvalán, Camilo (CGIAR System Organization, 2023)
The One CGIAR Research Initiative on “Rethinking Food Markets and Value Chains for Inclusion and Sustainability” commissioned a meta-study to review the available evidence and to identify knowledge gaps regarding the impacts on employment in agrifood value chains (AVC) integration and modernization processes in developing countries. This review included 290 texts, mostly journal articles, but also book chapters and reports.